Fecal Microbiota Transplantation. Issue 1 (July 2015) - Vandenplas, Yvan; Pierard, Denis; De Greef, Elisabeth
<x xml:space="preserve">Abstract</x> ABSTRACT The risks and advantages of the administration of fecal material of healthy people to patients are heavily debated. In adults, recurrent Clostridium difficile has become an accepted indication. In addition to all of the possible indications, many other questions need to be answered before pediatric indications and recommendations can be established. Optimal donor selection, fresh versus frozen stools versus capsules containing only microbiota, volume, and route of administration are just a few examples of the areas with missing data to allow in formulating recommendations for fecal microbiota or fecal material administration in children. A careful but not-too-complex regulation is the first priority in order to minimize the risk of administration of fecal slurry from unselected donors at home without medical supervision.